2021
DOI: 10.3390/plants10030548
|View full text |Cite
|
Sign up to set email alerts
|

Use of Black Poplar Leaves for the Biomonitoring of Air Pollution in an Urban Agglomeration

Abstract: Trees are considered to be an effective tool for metal pollution biomonitoring. In the present study, the concentration of metals (Cu, Pb, Zn, Cd, Co, Ni, Fe, Mn, and Al) in black poplar leaves (Populus nigra L.), together with the concentration of PM10, PM2.5, PM1, and total suspended particles (TSP), was used for the air pollution biomonitoring in 12 sites from various areas of Cluj-Napoca city, Romania. The concentration of PM10 in the air was high, but their metal content was low. However, Cu, Pb, and Zn w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Metal taken up by plants can concentrate in leaves and in roots [18]. Poplar tree (Poplar nigra) leaves are one of the most effective environmental bioindicators due to their sensitivity to heavy metal pollution [19] where heavy metal concentration in leaves are observed to be proportional to the heavy metal concentrations in soil. The relationship between heavy metal pollution in soil and heavy metal concentrations in the leaves of trees was studied in Yazd, Iran [14].…”
Section: Water and Soil Pollutionmentioning
confidence: 99%
“…Metal taken up by plants can concentrate in leaves and in roots [18]. Poplar tree (Poplar nigra) leaves are one of the most effective environmental bioindicators due to their sensitivity to heavy metal pollution [19] where heavy metal concentration in leaves are observed to be proportional to the heavy metal concentrations in soil. The relationship between heavy metal pollution in soil and heavy metal concentrations in the leaves of trees was studied in Yazd, Iran [14].…”
Section: Water and Soil Pollutionmentioning
confidence: 99%
“…But indirectly some of these research indicate also the practical potential of poplars for use in anthropogenic environments. The conducted review of the literature revealed that poplars offer significant potential in current research for providing ecosystem services and mitigating pollutants in urban areas, recognized for their role in improving air quality and acting as natural barriers for contaminant retention [77,[83][84][85][86][87]. In cities, poplars are valuable trees for:…”
Section: Resultsmentioning
confidence: 99%
“…technical and shielding functions, phytoremediation, windbreaks, anti-snow, anti-erosion and others). In Poland for instance it is estimated, that at that time the share of various poplars' taxa in shelterbelts and woodlots reached up to ¼ (25%) of total trees species amount [77,84,[117][118][119]. The obtaining objective was to achieve the desired effect in the possible shortest time!…”
Section: The Fast Increments Of Poplarsmentioning
confidence: 99%
“…These authors, however, found relatively large variation in metal accumulation among species. Similarly, Levei et al [ 28 ] found substantial inter-species differences in metal concentrations in leaves of Populus nigra, e.g., with respect to Pb.…”
Section: Introductionmentioning
confidence: 92%